2007
DOI: 10.1093/ndt/gfm007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the chemokine receptor CCR1 in human renal allografts

Abstract: CCR1 mRNA expression was associated with renal function in allografts. CCR1 protein expression was restricted to monocytes, CD20-positive B cells and DC-SIGN-positive dendritic cells. Thus most interstitial macrophages were CCR1 negative, which may relate to down-regulation after migration into the interstitium in human renal allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
9
2
Order By: Relevance
“…BDCA-1 + , BDCA-2 (CD303) + , and DC-LAMP (DC-lysosomal associated membrane protein 3, CD208) + cells have also been identified with in acutely rejecting renal allografts168. CCR1 + DC-SIGN + DC are also evident following transplantation169. A recent publication demonstrated increased CD141 hi CLEC9A + and CD1c + CD1a - DCSIGN - mDC170, as well as pDC in human allograft biopsies with histological evidence of fibrosis.…”
Section: Renal DC and Mac In Human Health And Diseasementioning
confidence: 99%
“…BDCA-1 + , BDCA-2 (CD303) + , and DC-LAMP (DC-lysosomal associated membrane protein 3, CD208) + cells have also been identified with in acutely rejecting renal allografts168. CCR1 + DC-SIGN + DC are also evident following transplantation169. A recent publication demonstrated increased CD141 hi CLEC9A + and CD1c + CD1a - DCSIGN - mDC170, as well as pDC in human allograft biopsies with histological evidence of fibrosis.…”
Section: Renal DC and Mac In Human Health And Diseasementioning
confidence: 99%
“…Recipient-derived B cells and B cell clusters (along with B cell transcripts) have been found in acute and chronically rejecting solid organ allografts where they can contribute to both humoral and cellular allograft rejection ( 53 56 ). Chemokines and chemokine receptors are critical in leukocyte recruitment, activation, and differentiation, with CXCL10 ligand and its receptor CXCR3 ( 57 ) as well as CXCL13 and CXCR5 ( 58 ) and chemokine receptor CCR1 ( 59 ) governing the recruitment of B cells. Gene expression profiling of renal allograft biopsies has shown that expression of these chemokines plus their corresponding receptors is strongly correlated with rejection than with stable allograft function ( 60 ).…”
Section: Induction and Formation Of Tlos—the Playersmentioning
confidence: 99%
“…Immunohistochemistry and double-immunofluorescence was performed as previously described. 73,74 Anti-human LTb mAb (Clone B27, Biogen), anti-human LTbR (RPA481Hu, Hölzel Diagnostika, Köln, Germany), anti-human CD20 mAb (clone L26, DakoCytomation, Dako Deutschland, Hamburg, Germany), CD3 (CD3-12, Serotec, Oxford, UK), anti-Aquaporin-1 (Millipore, Temecula, CA), and secondary reagents from Alexa Fluor (Life Technologies, Carlsbad, CA) were used. Archival biopsies were included from patients with pauci-immune cGN (n ¼ 10), IgA nephropathy (n ¼ 8), lupus nephritis (n ¼ 8), and membranous nephropathy (n ¼ 10).…”
Section: Immunohistochemistry On Human Tissuementioning
confidence: 99%